Make more, worry less : secrets from 18 extraordinary people who created a bigger income and a better life - Moss, Wes (FT Press, 2008)
Make More. Worry Less. Everyone wants to do that--but how? And how can you do it within the organization, where most people will spend their entire working lives? This book has the answers. No academic theory here: Make More, Worry Less brings together 18 riveting stories from people who've achieved both of these goals, gaining surprising wealth and real peace of mind along the way. These aren't superheroes. They're ordinary people who've done the extraordinary: from fast-food worker Linda Robb, now earning a six-figure income at Aflac, to once lowly telemarketer Steve Hudson, now running business development at one of the most promising start-up companies in the nation. Author and radio host Wes Moss reveals the powerful lessons these individuals have learned. Better yet, he shows how you can use those lessons to take ownership of your life and career, earning more money than you ever thought possible. But that's only half the equation! Moss also shows how to handle your increased success with less stress, fewer worries, and greater happiness. Every single story in this book is accompanied by specific tips, tricks, steps to take, and mistakes to avoid: actionable information you can use right now. If you want to change your life, start right here. Harness what you have Find it, create it, or tweak what you have Underestimate your obstacles Stop wasting time thinking about what you can't do Notice your network--and make the most of it Earning friendships, building alliances, finding mentors Take the first step, today You know what to do: learn how to get past whatever's stopping you.